Nitrate Intake Promotes Shift in Muscle Fiber Type Composition during Sprint Interval Training in Hypoxia - De Smet, Stefan; Van Thienen, Ruud; Deldicque, Louise; James, Ruth; Sale, Craig; Bishop, David J.; Hespel, Peter (Frontiers in Physiology, 2016)
Purpose: We investigated the effect of sprint interval training (SIT) in normoxia, versus SIT in hypoxia alone or in conjunction with oral nitrate intake, on buffering capacity of homogenized muscle (βhm) and fiber type distribution, as well as on sprint and endurance performance. Methods: Twenty-seven moderately-trained participants were allocated to one of 3 experimental groups: SIT in normoxia (20.9% FiO2) + placebo (N), SIT in hypoxia (15% FiO2) + placebo (H), or SIT in hypoxia + nitrate supplementation (HN). All participated in 5 weeks of SIT on a cycle ergometer (30-s sprints interspersed by 4.5 min recovery-intervals, 3 weekly sessions, 4-6 sprints per session). Nitrate (6.45 mmol NaNO3) or placebo capsules were administered 3 h before each session. Before and after SIT participants performed an incremental VO2max test, a 30-min simulated cycling time-trial, as well as a 30-s cycling sprint test. Muscle biopsies were taken from m. vastus lateralis. Results: SIT decreased the proportion of type IIx muscle fibers in all groups (P < 0.05). The relative number of type IIa fibers increased (P < 0.05) in HN (P < 0.05 vs. H), but not in the other groups. SIT had no significant effect on βhm. Compared with H, SIT tended to enhance 30-s sprint performance more in HN than in H (P = 0.085). VO2max and 30-min time-trial performance increased in all groups to a similar extent. Conclusion: SIT in hypoxia combined with nitrate supplementation increases the proportion of type IIa fibers in muscle, which may be associated with enhanced performance in short maximal exercise. Compared with normoxic training, hypoxic SIT does not alter βhm or endurance and sprinting exercise performance.